Research progress in fatigue behavior of soda lime/aluminosilicate glass - WANG Min-bo; JIAGN Liang-bao; LI Xiao-yu; LIU Jia-xi; LI Jia-ming; FU Zi-yi; YAN Yue (Cailiao gongcheng, 2021)
Soda lime/aluminosilicate glass is widely used in commercial and national defense industries due to its excellent physical properties such as high strength and high hardness. Fatigue fracture is one of the main failure modes of glass. Investigating the fatigue behavior is of great importance to its processing, life prediction and failure prevention. In this paper,the fundamental and experimental methods of static fatigue and dynamic fatigue of soda lime/aluminosilicate glass were reviewed.The conclusions obtained by comparing the fatigue behavior of soda lime silicate and aluminosilicate glass demonstrate that the threshold load for radial crack initiation of raw soda lime silicate glass is much lower than raw aluminosilicate glass, the threshold load for radial crack initiation of chemically strengthened soda lime/aluminosilicate glass is increased with the surface compressive stress; the crack growth rate of raw soda lime/aluminosilicate glass increase with fictive temperature and this phenomena is more evident in aluminosilicate glass; the raw soda lime/aluminosilicate glass shows a loading rate-dependent strength while the chemically strengthened aluminosilicate glass does not. Consequently, the effect of different stress state and environment atmosphere on the behavior of static fatigue and dynamic fatigue of static fatigue and dynamic fatigue is an important issue to be studied.